2018
DOI: 10.1073/pnas.1718211115
|View full text |Cite
|
Sign up to set email alerts
|

Complex electrophysiological remodeling in postinfarction ischemic heart failure

Abstract: Heart failure (HF) following myocardial infarction (MI) is associated with high incidence of cardiac arrhythmias. Development of therapeutic strategy requires detailed understanding of electrophysiological remodeling. However, changes of ionic currents in ischemic HF remain incompletely understood, especially in translational large-animal models. Here, we systematically measure the major ionic currents in ventricular myocytes from the infarct border and remote zones in a porcine model of post-MI HF. We recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 29 publications
9
86
1
Order By: Relevance
“…In spite of its relative importance, many aspects of I Na-late are still poorly understood. In contrast to the detailed data obtained in rabbit [18], guinea pig [19] and porcine [20] myocytes, we have only a limited number of recordings of native human and canine I Na-late , since these experiments were typically performed using conventional voltage clamp arrangements and many of them at room temperature [7,8,[21][22][23]. Self action potential voltage clamp measurements, delivering the cell's own AP as a command signal, are not available in the literature either for canine or human ventricular cardiomyocytes.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In spite of its relative importance, many aspects of I Na-late are still poorly understood. In contrast to the detailed data obtained in rabbit [18], guinea pig [19] and porcine [20] myocytes, we have only a limited number of recordings of native human and canine I Na-late , since these experiments were typically performed using conventional voltage clamp arrangements and many of them at room temperature [7,8,[21][22][23]. Self action potential voltage clamp measurements, delivering the cell's own AP as a command signal, are not available in the literature either for canine or human ventricular cardiomyocytes.…”
Section: Introductioncontrasting
confidence: 73%
“…Regarding undiseased human ventricular cells, this is the first report using the APVC technique. Our most important finding was to demonstrate that canine myocytes can be used as a reasonably good model to study human I Na-late -in contrast to myocytes originating from other mammals including guinea pigs, rabbits and pigs, since all in these latter species the current displays a crescendo profile [18][19][20]. Important implication of this interspecies difference is that the relative contribution of I Na-late to action potential morphology (with the concomitant Na + and Ca 2+ load resulting in increased arrhythmia propensity) increases with lengthening of APD in the "crescendo" group in contrast to the "decrescendo" situation, and vice versa, it will be relatively smaller at shorter APDs.…”
Section: Discussionmentioning
confidence: 99%
“…; Hegyi et al . ). Perhaps a similar approach might be useful to determine how different MCET pathways stratify in time and force hierarchies.…”
Section: Perspectivesmentioning
confidence: 97%
“…strain, stress, location, magnitude) imposed on the myocyte and determine which MCET pathway is operative by pharmacological or genetic dissection. Sequential application of specific channel blockers enabled electrophysiologists to 'peel back' the layers of ionic currents that underlie the action potential (Banyasz et al 2011;Hegyi et al 2018). Perhaps a similar approach might be useful to determine how different MCET pathways stratify in time and force hierarchies.…”
Section: Plurality Of Mechano-chemo-electro-transduction Pathwaysmentioning
confidence: 99%
“…Experiments with isolated canine myocytes from the BZ 5 days after MI have shown that a decrease in repolarizing currents prolongs APD (10). However, recent experimental evidence has demonstrated that a shift in balance between inward and outward currents acts to shorten APD in the BZ while prolonging APD in remote zones (40). In contrast to the single-cell level, there is little compelling evidence for APD prolongation in the BZ of chronic infarct regions, particularly in the human ventricle (24).…”
Section: Arrhythmogenesis By Prolonged Apdmentioning
confidence: 99%